Development of students’ vocational competence in the frame of extracurricular activities - Kolchenko, Kateryna; Kozlikovska, Nadiia (Social Welfare: Interdisciplinary Approach, 2012)
One of the most important conditions of future specialist’s vocational competence is a well-balanced combination of learning, scientific research and practice, which is not easy to achieve in terms of traditional education. Extracurricular activity in the form of educational-scientific-production student units (ESPSU) favours both active and creative learning of theory and practical skills formation vital for students’ further vocational activity. Six-year experience of extracurricular activities in Open International University of Human Development “Ukraine” shows ESPSU participants’ positive results comparing to other students in their academic achievements, professionalism and career development.
Keywords: professional qualifications; extracurricular activities; career development